Patient-reported outcomes of serum eye drops manufactured from Australian blood donations and packaged using Meise vials - Gemelli, Carley N.; Mondy, Phillip; Kakkos, Athina; O’Donovan, Justine; Diaz, Perfecto; Knight, Elizabeth; Hirani, Rena (Frontiers in Medicine, 2023)
Introduction: Serum eye drops (SED) are an effective treatment for dry eye syndrome. However, autologous serum collection can have challenges. Patient-tailored (allogeneic) SED (PT-SED) can be made from healthy blood donors. Australian Red Cross Lifeblood has manufactured both autologous SED (Auto-SED) and PT-SED and in May 2021, introduced Meise vial packaging. This study aimed to explore SED patient-reported outcomes and vial packaging satisfaction. Methods: A prospective cohort study was conducted with recruitment between 1 November 2021 and 30 June 2022. Participants completed the dry eye questionnaire (DEQ5), health-related quality-of-life (SF-8TM), Functional Assessment of Chronic Illness Therapy (FACIT-TS-G) and general wellbeing surveys. Existing patients completed these once and new patients were surveyed at baseline, 3- and 6-months post-treatment. Results: Participants who completed all study requirements were 24 existing and 40 new Auto-SED and 10 existing and 8 new PT-SED patients. Auto-SED patients were younger (56.2(±14.7) years) than PT-SED patients (71.4(± 10.0) years). Participants used a mean of 1.8(±1.1) SED drops, 5.3(± 2.9) times per day. In new patients, DEQ5 scores improved within 6-months from 14.0(±2.9) to 10.6(±3.4) for Auto-SED and from 12.9(±3.7) to 11.4(±2.8) for PT-SED. General wellbeing measures improved in new Auto-SED from 7.0(±1.9) to 7.8(±1.7) but reduced for new PT-SED from 6.7(±2.9) to 6.1(±2.9). Discussion: SED improved dry eye symptoms in most patients regardless of the serum source. Patients using PT-SED showed decreases in some quality-of-life measures however, recruitment was reduced due to operational constraints and concurrent comorbidities were not assessed. General feedback for SED and vial packaging was positive, with some improvements identified.